Penerapan Metode Pencatatan Berorientasi Sumber untuk Dokumentasi Asuhan Keperawatan di RSUD Dr. R. Koesma Tuban - Tiara Putri Ryandini; Lukman Hakim; Mukhamad Nurhadi; Mei Widyawati; Dyah Pitaloka (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Nursing care documentation is a crucial element in quality nursing practice. Dr. R. Koesma Tuban Regional General Hospital (RSUD), as a healthcare institution committed to quality care, introduces the source-oriented recording method to enhance the quality of nursing care documentation. This article presents an introduction to the importance of nursing care documentation, along with the background, objectives, and benefits of implementing this method at RSUD Dr. R. Koesma Tuban. The Literature review supports the decision to implement this method, highlighting its benefits in improving accuracy, compliance, care coordination, and healthcare service efficiency. The structured implementation method involves team training, document review, socialization, implementation, monitoring, evaluation, and advanced training. The implementation results indicate improvements in accuracy, compliance, care coordination, and healthcare service efficiency. In conclusion, the application of the source-oriented recording method at RSUD Dr. R. Koesma Tuban is a strategic step to enhance the quality of healthcare services and patient safety.